Multicenter Evaluation of Clinical Efficacy and Safety of Per-oral Endoscopic Myotomy in Children. Issue 5 (November 2019) - Choné, Adrien; Familiari, Pietro; von Rahden, Burkhard; Desai, Pankaj; Inoue, Haruhiro; Shimamura, Yuto; Eleftheriadis, Nikos; Yamashita, Kanefumi; Khashab, Mouen A.; Shiwaku, Hinorari; Seewald, Stefan; Draganov, Peter V.; et al.
ABSTRACT: Objectives: Per-oral endoscopic myotomy (POEM) is a recommended treatment modality for achalasia, but there is little published data for its use in children. The objective of the present study was to evaluate whether POEM is clinically effective and safe for children. Methods: International multicenter retrospective study conducted in 14 tertiary centers that included consecutive children who underwent POEM between January 2012 and August 2018. Outcomes, such as clinical response were assessed whenever available. Adverse events and factors associated with clinical failure were also investigated. Results: A total of 117 patients (mean ± SD age: 14.2 ± 3.7 years) underwent POEM for achalasia (type I, n = 36; type II n=66; type III, n=8). Among these, 30 (26%) were pretreated (botulinum injection and/or pneumatic dilatation). Mean ± SD baseline Eckardt score was 7.5 ± 2.0. Clinical success was achieved in 90.6% of cases (95%CI [83.8%;95.2%]) in the intention-to-treat analysis. The mean ± SD Eckardt score post-POEM was 0.9 ± 1.2 ( P < 0.001). The mean duration of follow-up time 545 days (range: 100–1612). A total of 7 adverse events occurred (4 mucosotomies, 2 subcutaneous emphysema, 1 esopleural fistula). Gastroesophageal reflux symptoms were seen in 17 patients (15%); missing data for 10 patients (9%). There was a trend towards more frequent clinical failure in achalasia associated with genetic disorders (40% vs 8%, P = 0.069). Conclusions: POEM in pediatric patients appears to be effective and safe, although there was a trend towards more frequent clinical failure achalasia associated with genetic disorders. Further studies are needed to assess the long-term outcomes, especially the consequences of GERD.